Transdisciplinary and interdisciplinary exchanges between embodied cognition and performance practice: working across disciplines in a climate of divisive knowledge cultures. Issue 1 (2nd January 2017) - Bryon, Experience
ABSTRACT: Although Embodied Cognition and Performance Practice could be said to have in common that they live in the fields of hermeneutics and epistemology concurrently, and with this are interested in perception, knowledge, experience and agency without privileging any of them or presuming a linear or status relationship among them -- there still remains a divisive disciplinary gulf. This paper provides a critical history of the science/humanities divide, exposing prejudices and practices that often impede productive interdisciplinary relationships between Cognitive Science and Performance, and offers suggestions forward towards a more productive middle field allowing for the possibility of new knowledge(s).